PERTANGGUNGJAWABAN MYANMAR ATAS TINDAKAN GENOSIDA TERHADAP KELOMPOK ETNIS ROHINGYA BERDASARKAN GENOCIDE CONVENTION 1948 - Intan Ghina Maurizka; Ida Kurnia (Jurnal Hukum Adigama, 2020)
The United Nations states that the act of genocide is a denial of the right to the existence of all human groups who are very conscience of mankind, resulting in great harm to mankind and contrary to moral law and the spirit and purpose of the United Nations. It has been 72 years since the adoption of the Genocide Convention, but these crimes are repeated today, such as the acts of genocide presented by the Rohingya Ethnic Group in Myanmar. Myanmar is a member country and has ratified the Genocide Convention. So as a state party to the convention, it must carry out its obligations, namely to prevent and punish acts of genocide. However, the actions taken by Myanmar as a member state are contrary to its obligations in all its capabilities to prevent and punish the crime of genocide. Researchers investigate these problems with normative legal research. The data investigates that Myanmar has responsibility for its actions and should make reparations.